Potensial Masjid Jammi Daruss Sadaah sebagai Tempat Pengembangan Masyarakat Tebing Tinggi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Mosques not only function as places of worship, but also have great potential to become centers of community development. This research examines the potential of the Jammi Daruss Saadah Mosque-the oldest mosque in Tebing Tinggi Sub-district, Empat Lawang Regency-in shaping the social, educational, spiritual and economic space of the local community. This research uses a qualitative approach with structured interview methods and participatory observation and is supported by an ethnographic approach to communication to understand the dynamics of social interactions that occur in the mosque environment. The results showed that this mosque has become the main forum for various community activities such as routine recitation, Al-Qur'an learning classes for children, and economic activities in the form of sacrificial animal farms managed by the mosque management. The mosque plays a role as a driver of improving the quality of religion and community welfare, as well as a symbol of the resilience of local Islamic identity since before independence until now. This finding emphasizes the importance of strengthening the function of the mosque as a social institution that is adaptive to the needs of the times. Mosques not only play a role in the spiritual realm, but also become strategic agents of community empowerment. This research recommends the need to strengthen mosque institutional governance and program innovation based on community participation so that the role of mosques can be optimized in responding to contemporary social challenges.